2021
DOI: 10.1097/pr9.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron–associated macrophages as novel modulators of neuropathic pain

Abstract: The peripheral nervous system comprises an infinity of neural networks that act in the communication between the central nervous system and the most diverse tissues of the body. Along with the extension of the primary sensory neurons (axons and cell bodies), a population of resident macrophages has been described. These newly called sensory neuron–associated macrophages (sNAMs) seem to play an essential role in physiological and pathophysiological processes, including infection, autoimmunity, nerve degeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 236 publications
(191 reference statements)
2
33
0
Order By: Relevance
“…There is plenty of evidence that monocyte-derived infiltrating macrophages and tissueresident peripheral nerve macrophages are involved in neuropathic pain following surgical injury of the sciatic nerves or spinal nerves [15,44,50,94]. We have shown that L5 spinal nerve injury causes macrophage accumulation in L4 DRG, in which macrophage-derived HMGB1 induces RAGE-dependent transcriptional upregulation of Ca v 3.2 T-type Ca 2+ channels in nociceptors, leading to neuropathic pain [50].…”
Section: Neuropathic Painmentioning
confidence: 87%
See 4 more Smart Citations
“…There is plenty of evidence that monocyte-derived infiltrating macrophages and tissueresident peripheral nerve macrophages are involved in neuropathic pain following surgical injury of the sciatic nerves or spinal nerves [15,44,50,94]. We have shown that L5 spinal nerve injury causes macrophage accumulation in L4 DRG, in which macrophage-derived HMGB1 induces RAGE-dependent transcriptional upregulation of Ca v 3.2 T-type Ca 2+ channels in nociceptors, leading to neuropathic pain [50].…”
Section: Neuropathic Painmentioning
confidence: 87%
“…The latter class of macrophages are present in tissues under homeostatic conditions. The bone marrow-derived infiltrating macrophages and tissue-resident macrophages have common and different roles in health and/or disease, and both of them are considered to participate in processing or modulation of pain signals [8,15]. The majority of tissues in the body contain tissue-resident macrophage populations that sense and respond to invading pathogens, environmental stressors or noxious stimuli, and are also essential in tissue development, homeostasis, remodeling and repair [16][17][18][19][20].…”
Section: Circulating Monocyte-derived Infiltrating Macrophages and Tissue-resident Macrophages Including Spinal Microglia And Peripheral mentioning
confidence: 99%
See 3 more Smart Citations